Measurement of Higgs production cross section via vector boson fusion in H → ZZ → 4l final state at 13 TeV using artificial neural networks - Almeida, Miquéias Melo de (2019)
This work presents an isolated measurement of the Higgs boson production cross section via Vector Boson Fusion (VBF) production mode, with the Higgs decaying through the H → ZZ → 4l(l = e, µ) channel. The study is performed using data samples corresponding to an integrated luminosity of 35.9 fb−1 from pp collisions at √s = 13 TeV, which has been collected by the CMS experiment during 2016 at the LHC. A multivariate analysis is performed through the usage of Artificial Neural Networks (ANNs). Statistical shape analysis of ANNs developed for two orthogonal jet-based categories is done by combining the discriminants distribution from each category. The Higgs VBF signal strength modifier is measured to be µqqH = 1.28+1.24−0.84 for an expected Higgs boson of mH =125GeV. This result is compatible with the SM expectation. The observed significance of the present analysis is Z obs qqH = 1.9, while the expected one is Z exp qqH = 1.8. The observed and expected 95%CL limits are estimated as µ obs qqH < 3.79 and µ exp qqH < 1.66, respectively. A projection for future luminosities is also presented and it is expected that the presente analysis will have enough significance for the VBF Higgs production evidence (3.4σ) at 150 and the observance (5.1σ) at 359 fb−1, respectively. Additionally, the present work brings on its appendixes full results obtained by the author during his collaboration in one of the CMS L1 Tacking Trigger approaches in 2015 and 2016, which has been leaded by Fermilab. The appendixes also contains a summary of results obtained by the author when working on an event tagging procedure called FastME, which is based on Monte Carlo events topology.